Faktor-Faktor yang Berpengaruh terhadap Brand Image ditinjau dari Komunikasi Pemasaran - Hardyansyah, Robby; selviana, Inggrid; Budiputranto, Radhitya (Universitas Batanghari Jambi, 2024)
This research aims to describe each influence of the marketing mix starting from public relations advertising, personal selling, public relations and direct marketing on a company's brand image. This research uses literature review techniques with a descriptive qualitative approach. Search for literature using the Google search engine and Google Scholar with the keywords